A Flexible Pellet Injection System for the Tokamak JT-60SA: The Final Conceptual Design. (3rd April 2019) - Lang, P. T.; Nakano, T.; Garzotti, L.; Pégourié, B.; Ploeckl, B.; Sakurai, S.
Abstract: The research plan of the JT-60SA, a superconducting tokamak device currently under construction, requests a powerful pellet injection system for its particle fueling and edge-localized-mode (ELM) pacing experiments. These investigations, foreseen to answer basic questions with respect to the operation of ITER and a future fusion power plant like DEMO, need pellets with flexible parameters delivered precisely and reliably for control purposes. Here, we present a conceptual design of this system based on classical pellet technology. Analysis showed pellets will show the best performance for fueling and most likely also for ELM pacing when injected from the torus inboard side, despite the limited maximum pellet speed caused by this approach. This is due to constructional constraints rising from the fact the JT-60SA vacuum vessel is already under construction, enforcing inboard injection via a multibend guiding-tube system and limiting the maximum pellet speed to about 470 m/s. To match this boundary condition and fulfill the need for precise control, a centrifuge accelerator has been chosen. Based on the stop cylinder principle and equipped with a double accelerator arm, it can host up to six steady-state ice extruders working simultaneously for pellet production. This way, all system requirements expressed in the research plan can be well covered, providing even some headroom for better flexibility during the planned investigations. Details of our design and the reasoning for the layout chosen are provided in this paper.